Clínica Ampliada e Compartilhada: a produção do cuidado em tentativas de suicídio, no entendimento dos profissionais da Rede de Atenção à Saúde de um município do centro-oeste paulista - Dovidauskas, Katarina Dudienas (Universidade Federal de São Carlos, 2024)
This research was conceived based on the observation of the recent increase in cases of psychological disorders in Brazil and, consequently, the rise in suicide attempts, a phenomenon that can be correlated with the Covid-19 pandemic. While suicide attempts were already considered a public health issue before, it is now noticeable in everyday healthcare work that the number of people exhibiting suicidal ideation and behaviors is rising. The reality of small municipalities in Brazil is no different. Alongside the increasing number of individuals experiencing mental distress, we observe, in the practice of Primary Health Care (PHC) and Emergency Services (ES) of the Brazilian Unified Health System (SUS), several obstacles in the care provided to users at risk of suicide, which violate the principles of integrality in health. In general, suicide remains a taboo subject in our society, which makes it less discussed and fosters distorted ideas, prejudice, stereotypes, stigma, and avoidant behaviors, resulting in difficulties in support, active listening, and comprehensive care for these users. In this context, the aim of this study was to understand how and whether care is provided to users who arrive at PHC and ES after a suicide attempt or with active suicidal ideation, and what the professionals of these services understand about this issue. The National Humanization Policy (PNH) establishes guidelines that orient health work from a perspective of continuous, comprehensive, and humanized care. To understand the professionals’ perception of the work performed in the Primary Care network, two reflective groups were conducted: one with PHC professionals and another with ES professionals, using a semi-structured questionnaire as a starting point to foster the dialogical construction of critical- reflective narratives. For the analysis of the collected data, the speeches were transcribed and thoroughly reviewed, in the light of Bardin's Thematic Analysis (Bardin, 1977/2016). The theoretical framework was based on the National Humanization Policy (PNH), linked to concepts from the National Primary Health Care Policy (PNAB). As a result, it became evident that the municipality participating in the research presents both strengths, in line with the guidelines of the National Humanization Policy (PNH), and weaknesses, such as the absence of shared responsibility within the network, the lack of a psychiatric emergency care pathway, and poor coordination between services. Through the network diagnosis, it was possible to present consistent data on the challenges and strengths identified by the professionals to the municipal management and propose a collaborative approach between sectors. Additionally, the study suggested expanding the training of these professionals in psychiatric emergencies and other complementary actions, such as evidence-based practice, public policies, and mental health promotion initiatives.
Expanded and Shared Clinic: the production of care in suicide attempts, according to professionals from the Health Care Network of a city in the center-west of São Paulo
Keywords: Integralidade em saúde; Atenção primária em saúde; Ideação suicida; Saúde mental; Acolhimento; Integrality in health; Primary health care; Suicidal ideation; Mental health; Support; CIENCIAS DA SAUDE